KARAKTERISTIK KIMIA DAN ORGANOLEPTIK COOKIES TEPUNG MOCAF (Modified Cassava Flour) DAN TEPUNG DAUN KELOR (Moringa oleifera) DENGAN VARIASI JENIS PEMANIS: Characteristics of Chemical and Organoleptic Properties of Mocaf Flour and Moringa Leaf Flour Cookies with Variation of Types Sweeteners - Suhartatik, Nanik; Mustofa, Ecio; Karyantina, Merkuria (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2025)
Cookies are one of the most popular foods in Indonesia. The taste tends to be sweet, the texture is crunchy, and it has a long shelf life. Generally, cookies are made from wheat flour which contains gluten. Mocaf is an alternative source of carbohydrates and a substitute for wheat flour. Moringa leaf powder was chosen because it is rich in protein, minerals and vitamins. The advantages of adding Moringa leaf flour can improve the quality of the cookies especially the fiber and protein. This study aims to formulate crispy cookies rich protein using moringa leaf and mocaf flour. This studied used two factorial complete randomized design (CRD) with two replications. The factors used were the ratio of moringa leaf flour: mocaf flour (2 : 98 ; 4 : 96 ; 6 : 94) and variations in the type of sweetener (can sugar, arenga sugar, palm sugar). The best cookies were found in samples with 6% moringa leaf and 94% mocaf flour with variations of palm sugar this product contain 5.20% of protein, 2.79% of moisture,1.44% of ash, 20.82% of fat, 3.30% of fiber, 69.74% of carbohydrate, color 4.55 (greenish yellow), taste 3.25 (sweet), aroma 3.90 (slightly unpleasant), crispness 2.55 (not very crispy). Mocaf flour and moringa leaf flour have the potential to increase the functional value of cookies.